That religion in which all men agree : freemasonry in American culture - Hackett, David G. (University of California Press, 2014)
Hackett weaves the story of Freemasonry into the narrative of American religious history. Coming to colonial America freighted with the mythical legacies of stonemasons' guilds and the Newtonian revolution, English Freemasonry brought with it a vast array of cultural baggage that was drawn upon in different ways, added to, and transformed during the fraternity's sojourn in American culture. This study argues that from the 1730s to the early 20th century, the changing beliefs and initiatory practices of this all-male society were broadly appropriated by the religious worlds of an evolving social order.